FAKTOR-FAKTOR PENYEBAB KEMATIAN PADA BAYI DAN ANAK DI BAWAH USIA LIMA TAHUN DI KOTA PEKALONGAN (STUDI KASUS DI KECAMATAN PEKALONGAN SELATAN) - Millatin Puspaningtyas; Ana Setyowati; Putri Andanawarih (JURNAL LITBANG KOTA PEKALONGAN, 2014)
Infant Mortality Rate (IMR) is one of the health indicators of a country. Pekalongan City Health Deparment data show that IMR in Pekalongan city in 2013 as many as 104 cases. Viewed from the side of the cause, there are two kinds of cause in infant and child mortality, they are endogenous and exogenous. The purpose of this research is to describe the causes of infant and child under five years old mortality in Pekalongan. Research carried out quantitatively and qualitatively, with respondent amounted to 20 persons. The main informants are 8 parents of infants or children who died in 2013-2014, and triangulation informants include 1) Independent Practic Midwife, 2) The Head of Space Baby, 3) The Head of Space Child, 4) The Head of Medical Records Unit. Quantitative data collection using medical record, KIA report, and data OVP, while qualitative using indepth interviews. Analysis of quantitative data presented in the table of descriptive and qualitative content analysis. The statistical results showed the mother’s education level is elementary (45%), housewives (70%), the incidence of low birth weight (20%), asphyxia (10%), and diarrhea (20%). Qualitative results showed that infant and child mortality due to exhausting household activities, insufficient nutrition, maternal health workers do not implement advice, information when ANC is less clear, less PHBS, and late treatment to referral facility. It is recommended for health workers to provide KIE should be deeper, clear, easy to understand an engange husband or family. Keyword : Basic concepts infants and children, cause of death